Sonographic assessment of nerve blood flow in diabetic neuropathy. Issue 2 (2nd August 2019) - Borire, A. A.; Issar, T.; Kwai, N. C.; Visser, L. H.; Simon, N. G.; Poynten, A. M.; Kiernan, M. C.; Krishnan, A. V.
What's new?: Alterations in nerve blood flow are implicated in the development of diabetic neuropathy, but in vivo techniques for its assessment are either invasive or complicated. Doppler ultrasound techniques have been shown to detect intraneural blood flow in nerve injury reliably, both in real‐time and non‐invasively. Interventions targeting intraneural blood flow may improve neuropathic symptoms in people with diabetes. Intraneural blood flow was reliably detected in 28% of people with diabetic neuropathy and correlated significantly with measures of neuropathy severity. Most of the people with detectable blood flow had moderate to severe neuropathy with prominent sensory symptoms. Intraneural blood flow is a reliable and reproducible biomarker for the assessment of diabetic neuropathy and may be a potential therapeutic target. Abstract: Aims: To undertake sonographic assessment of nerve blood flow in people with Type 2 diabetes and correlate the findings with neuropathy severity scores and electrophysiological measurements. Methods: Median and tibial nerve ultrasound scans were undertaken in 75 people with diabetes and 30 aged‐matched controls without diabetes, using a high‐resolution linear probe at non‐entrapment sites. Nerve blood flow was quantified using power Doppler techniques to obtain the vessel score and the maximum perfusion intensity. Neuropathy severity was assessed using a total neuropathy score. Results: Diabetic nerves had higher rates of nerve blood flow detection (28%) compared to the control group ( P < 0.0001). Significant correlations were found between nerve blood flow measurements and nerve size ( P <0.001), reported sensory symptoms ( P < 0.05) and neuropathy severity scores ( P < 0.001). The cohort with diabetes had significantly larger median (8.5 ± 0.3 mm 2 vs 7.2 ± 0.1 mm 2 ; P < 0.05) and tibial nerves (18.0 ± 0.9 mm 2 vs 12.8 ± 0.5 mm 2 ; P < 0.05) compared with controls. Conclusion: Peripheral nerve hypervascularity is detectable by ultrasonography in moderate to severe diabetic neuropathy with prominent sensory dysfunction.